Changing the narrative information campaigns, strategy and crisis escalation in the digital age - Freedman, Lawrence; Williams, Heather (Adelphi series, 2023)
Narratives provide the storylines of conflict and in doing so become an arena of conflict themselves. When states mount information campaigns against each other, they are trying to change the narrative. The digital platforms of the new information environment have been identified by various analysts as a significant factor in contemporary strategy and crisis management. But while social media is noisier and more chaotic than traditional media, and unprecedented in its immediacy and accessibility, has it thus far been a game changer in strategic affairs? In this Adelphi book, Sir Lawrence Freedman and Heather Williams examine the impact of state-led digital information - or disinformation - campaigns in four contexts: the India-Pakistan crisis over Kashmir in 2019; the heightened tensions between the United States and Iran following the assassination of Qasem Soleimani in 2020; China's messaging in response to the COVID-19 pandemic from 2020-22; and the Russia-Ukraine crisis from 2013-23. While noting the meaningful consequences of digital information campaigns, in each case the authors call for a sense of perspective. Such campaigns are only one aspect of wider political struggles. They are also difficult for their initiators to control, and less likely to influence foreign audiences than domestic ones. Overall, the authors argue, there is little evidence so far to suggest such campaigns will have as much influence over contemporary crises as the classical instruments of military and economic power.